2019
DOI: 10.1111/jam.14333
|View full text |Cite
|
Sign up to set email alerts
|

Virtual screening for quorum‐sensing inhibitors of Pseudomonas fluorescens P07 from a food‐derived compound database

Abstract: Aims: Pseudomonas fluorescens are important psychrotrophic food spoilage bacteria that are frequently detected in dairy, meat and aquatic products. Quorum sensing (QS) is an intercellular communication and gene regulation mechanism that enables bacteria to monitor their cell densities and regulate a variety of physiological processes. Hence, targeting the bacterial QS system might be a feasible approach to improve food quality and safety by regulating the spoilage caused by P. fluorescens. Methods and Results:… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 19 publications
(12 citation statements)
references
References 53 publications
0
12
0
Order By: Relevance
“…Ding et al [190,191] applied a molecular docking approach to screen potential QSIs from traditional Chinese medicine and food-derived compound databases (more than 13,000 molecules each), able to interfere with a three-dimensional (3D) structure of LuxI- and LuxR-type regulators; the latter was built by homology modelling using the amino acids sequences obtained through WGS of a P. fluorescens strain, causing spoilage of chilled raw milk and aquatic products. Results showed that benzyl alcohol, catechin, (-)-epicatechin, propyl gallate, hesperidin, and lycopene were identified as potent QSIs, and may be applied in food preservation and biofilm elimination.…”
Section: Strategies To Control the Spread Of Antibiotic Resistant mentioning
confidence: 99%
“…Ding et al [190,191] applied a molecular docking approach to screen potential QSIs from traditional Chinese medicine and food-derived compound databases (more than 13,000 molecules each), able to interfere with a three-dimensional (3D) structure of LuxI- and LuxR-type regulators; the latter was built by homology modelling using the amino acids sequences obtained through WGS of a P. fluorescens strain, causing spoilage of chilled raw milk and aquatic products. Results showed that benzyl alcohol, catechin, (-)-epicatechin, propyl gallate, hesperidin, and lycopene were identified as potent QSIs, and may be applied in food preservation and biofilm elimination.…”
Section: Strategies To Control the Spread Of Antibiotic Resistant mentioning
confidence: 99%
“…Epicatechin is a flavonoid commonly found in tea leaves and there are reports suggesting its antibacterial activity against Helicobacter pylori, Staphylococcus aureus, Pseudomonas aeruginosa, and Candida albicans. Moreover, recently it has been identified to serve as QSA in P. aeruginosa 28,[30][31][32][33][34] . Galangin is flavanol found in several medicinal plants and has a rich literature on its antibacterial activity against S. aureus 35 .…”
Section: Discussionmentioning
confidence: 99%
“…Most pqs-inhibitors have been identified via costly and timeconsuming biosensor-based screenings or via the rational design and experimental validation of AQ analogs or precursors based on the structure of PqsR and of AQ biosynthetic enzymes. Virtual screenings could reduce the time and costs associated to conventional drug discovery programs, hence in silico techniques have been extensively applied for the identification of molecules hampering the las QS system of P. aeruginosa (Yang et al, 2009;Skovstrup et al, 2013;Tan et al, 2013;Soheili et al, 2015;Gökalsın et al, 2017;Kalia et al, 2017;Xu et al, 2017) or QS systems in other bacteria (Zhu et al, 2012;Ali et al, 2018;Ding et al, 2018Ding et al, , 2019Medarametla et al, 2018). To the best of our knowledge, only synthetic quinoline-based molecules have so far been identified as PqsR antagonists by means of in silico docking analyses (Soukarieh et al, 2018a).…”
Section: Discussionmentioning
confidence: 99%